Anostomoides passionis, a new fish species from rio Xingu, Brasil (Characiformes: Anostomidae) - Santos, Geraldo M.d.; Zuanon, Jansen (Zootaxa, 2006)
We describe Anostomoides passionis, a new species of anostomid fish from rio Xingu. The species attains 306 mm SL and is distinguished from the other two congeneric species by the lateral line scale count (38–39, instead of 39–41 in A. atrianalis and 42–44 in A. laticeps) and by the color pattern: brownish-grey with two round to heart-shaped, dark blotches on the side (a larger one under the dorsal fin and another above the origin of the anal fin). Anostomoides passionis inhabits rocky stretches of the rio Xingu with moderate to high current. Stomach contents of two specimens of A. passionis caught during the low water season were composed mainly of fragments of sponges.